1999
DOI: 10.1107/s0907444998013699
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the catalytic site mutants D99A and H48Q and the calcium-loop mutant D49E of phospholipase A2

Abstract: Crystal structures of the active-site mutants D99A and H48Q and the calcium-loop mutant D49E of bovine phospholipase A 2 have been determined at around 1.9 A Ê resolution. The D99A mutant is isomorphous to the orthorhombic recombinant enzyme, space group P2 1 2 1 2 1 . The H48Q and the calciumloop mutant D49E are isomorphous to the trigonal recombinant enzyme, space group P3 1 21. The two active-site mutants show no major structural perturbations. The structural water is absent in D99A and, therefore, the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…onstrate that the secondary, tertiary and quaternary structures of the native, recombinant wild-type and mutant rBthTx-I proteins are indistinguishable. This conclusion is in agreement with previous site-directed mutagenesis results in bovine pancreatic class II Asp%*-PLA # , which also demonstrated that mutations in the active-site region do not perturb significantly the global structure of the protein [16,41].…”
Section: Figure 2 Far-uv CD Spectra (A) and Intrinsic Tryptophan Fluosupporting
confidence: 93%
“…onstrate that the secondary, tertiary and quaternary structures of the native, recombinant wild-type and mutant rBthTx-I proteins are indistinguishable. This conclusion is in agreement with previous site-directed mutagenesis results in bovine pancreatic class II Asp%*-PLA # , which also demonstrated that mutations in the active-site region do not perturb significantly the global structure of the protein [16,41].…”
Section: Figure 2 Far-uv CD Spectra (A) and Intrinsic Tryptophan Fluosupporting
confidence: 93%
“…Virus preparations were incubated with purified sPLA 2 -X or a different catalytically inactive mutant, ⌬3sPLA 2 -X (H46N, D47E, and Y50F mutations) (9,19), prior to infection of the human T-cell leukemia cell line A3R5, a subline of A3.01 cells (10) expressing both CCR5 and CXCR4. Flow cytometric analysis of intracellular Gag protein was used to assess viral replication.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the bovine pancreatic PLA2 and its mutant structures studied so far, 5,22,27,33,34 the surface loop residues were always found to be disordered, except in the high-resolution (1.5 Å ) orthorhombic form 26 of the recombinant PLA2. Again in the present free triple mutant structure, the electron density is not clear and the surface loop residues are disordered.…”
Section: Ordered Surface Loopmentioning
confidence: 98%
“…The surface loop residues (60 -70) and the calcium-binding loop(27)(28)(29)(30)(31)(32)(33)(34) are indicated with the residue numbers at the beginning as well as at the ends. This Figure was produced using the program MOLSCRIPT 44.…”
mentioning
confidence: 99%